2018
DOI: 10.3389/fmed.2018.00290
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fibromyalgia in Spondyloarthritis: From Classification Criteria to Outcome Measures

Abstract: The term spondyloarthritis (SpA) encompasses a broad clinical spectrum characterized by chronic inflammatory conditions affecting the sacroiliac joints, the spine but also peripheral joints and tendons and being additionally associated with the involvement of organs, such as bowel, eye and skin (1). Musculoskeletal pain is a key symptom in SpA. However, although low back pain and/or joint pain are characteristic for SpA, undifferentiated pain at different enthesial sites may also be a concomitant or even the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…(38,40,41) Because symptoms of central sensitization overlap those of inflammatory rheumatic diseases, it can be challenging to determine disease severity due to the primary rheumatic disease vs the burden of central sensitization, particularly when evaluating outcome measures that rely on patient-reported symptoms. (38,42,43) For example, it may be difficult to distinguish true enthesitis resulting from inflammation of the entheses vs entheseal tenderness due to central sensitization when using clinical examinations that rely on palpitation of tender entheseal insertion sites. Use of imaging techniques and development of more sensitive screening tools may help improve differentiation between central sensitization and axSpA or other rheumatic diseases in the future, but these methods are not commonly employed in longitudinal observational cohort studies due to time and cost.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…(38,40,41) Because symptoms of central sensitization overlap those of inflammatory rheumatic diseases, it can be challenging to determine disease severity due to the primary rheumatic disease vs the burden of central sensitization, particularly when evaluating outcome measures that rely on patient-reported symptoms. (38,42,43) For example, it may be difficult to distinguish true enthesitis resulting from inflammation of the entheses vs entheseal tenderness due to central sensitization when using clinical examinations that rely on palpitation of tender entheseal insertion sites. Use of imaging techniques and development of more sensitive screening tools may help improve differentiation between central sensitization and axSpA or other rheumatic diseases in the future, but these methods are not commonly employed in longitudinal observational cohort studies due to time and cost.…”
Section: Accepted Articlementioning
confidence: 99%
“…Use of imaging techniques and development of more sensitive screening tools may help improve differentiation between central sensitization and axSpA or other rheumatic diseases in the future, but these methods are not commonly employed in longitudinal observational cohort studies due to time and cost. (38,42) Distinguishing the degree of symptoms due to central sensitization from that of axSpA is important to guide treatment decisions and accurately assess treatment response.…”
Section: Accepted Articlementioning
confidence: 99%
“…An alternative explanation is that having fibromyalgia distorts the measures used to assess axSpA. Indeed, Alluno et al [27] demonstrated that measures thought to be disease specific such as the Bath indices are not axSpA specific. However it is unlikely that this can entirely account for the current observations.…”
Section: Discussionmentioning
confidence: 99%
“… 48 For this reason, objective measures, such as C-reactive protein (CRP), and the Ankylosing Spondylitis Disease Activity Score play a key role in discriminating between pain caused by inflammatory activity and pain due to the interference of FM. 49 …”
Section: Introductionmentioning
confidence: 99%